Odontogenic cysts decompression: Myth or reality? A case report - Samir Mainassara Chekaraou; Abdoul-Hafizou Rabe Amani; Abdoul-Majid Habibou; Malika Mascou; Amadou Ali; Abarchi Boubé Djafarou; Inoussa Daouda Bako; Kadre Ousmane Kadre Alio; Mahamadou Dandi Abarchi (Elsevier, 2024)
Introduction: Odontogenic cysts are cysts that originate from the odontogenic epithelium and are found in the areas of the jaw that bear teeth. Dentigerous cysts are one of the most common developmental types of odontogenic cysts occurring in the oral cavity and often manifest as incidental findings on dental radiographs and/or as asymptomatic swellings. Treatment usually involves cyst enucleation or tooth extraction, although decompression may be used for larger lesions. Case report: We report the case of an 8-year-old patient referred by his ENT physician following the swelling of the left maxilla for whom the clinical, radiological examination associated with biopsy suggested a dentigerous cyst. Conclusion: management consisted of decompression of the lesion after eight months which allowed the disappearance of the cystic. The patient continues to be followed clinically and radiologically.